Virtual eye: helping the visually impaired map the real world - Singh Aishwarya (Nanyang Technological University, 2023)
This report discusses the design and implementation of an enhanced indoor navigation system to improve existing technology by aiding the visually impaired. Loss of vision can drastically impair an individual's sense of direction and mobility, especially in unfamiliar surroundings. Due to this, visually impaired individuals often find themselves needing further support and time to gain familiarity with new indoor settings. This report aims to present an enhanced indoor navigation system, customized to cater to the needs of the visually impaired. This has been achieved through the use of Bluetooth Low Energy (BLE) beacons, a BLE-supported Android device with in-built motion sensors, and an Android Mobile Application. The mobile application can be operated in three different modes – regular navigation, assisted navigation, and free-roam mode. The current implementation of the application supports navigation at Level 1 of the School of Computer Science and Engineering (SCSE). BLE beacons are placed at important landmarks of this environment, and the user is provided with a list of destinations for navigation. User interaction, feedback, and the effectiveness of the proposed indoor navigation system have been evaluated in this report. Experimental results and observations indicate an improvement in indoor navigation with the introduction of VirtualEYE, the Android Mobile Application.